2013
DOI: 10.1152/jn.01041.2012
|View full text |Cite
|
Sign up to set email alerts
|

Development of on-off spiking in superior paraolivary nucleus neurons of the mouse

Abstract: Felix RA 2nd, Vonderschen K, Berrebi AS, Magnusson AK. Development of on-off spiking in superior paraolivary nucleus neurons of the mouse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 89 publications
1
35
0
Order By: Relevance
“…Thus, the MNTB likely is a major part of both binaural “where” processing pathways that include the LSO and monaural “what” pathways of which the SPN is a part (Schofield, 2005). Future studies are necessary to determine whether other monaural areas implicated in auditory object identification such as the octopus cells of the cochlear nucleus (Felix et al, 2013) also receive dopaminergic inputs. Conversely, regions like the bushy cell area of the cochlear nucleus that give rise to binaural pathways (Cant and Benson, 2003) may be devoid of dopaminergic input.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the MNTB likely is a major part of both binaural “where” processing pathways that include the LSO and monaural “what” pathways of which the SPN is a part (Schofield, 2005). Future studies are necessary to determine whether other monaural areas implicated in auditory object identification such as the octopus cells of the cochlear nucleus (Felix et al, 2013) also receive dopaminergic inputs. Conversely, regions like the bushy cell area of the cochlear nucleus that give rise to binaural pathways (Cant and Benson, 2003) may be devoid of dopaminergic input.…”
Section: Discussionmentioning
confidence: 99%
“…This is achieved by plotting one time-dependent variable against another time-dependent variable. In practice, the voltage is plotted against dV/dt to describe the spiking and bursting activity (Chagnaud et al 2011;Felix et al 2013;Pinsker and Bell 1981). To visualize the changes in the slow oscillation before and after blocking I h , we applied a lowpass filter on voltage traces to filter out all action potentials, and then plotted voltage against dV/dt and dV/dt against d 2 V/ dt 2 using filtered slow oscillation traces.…”
Section: Phase-plane Diagrams Showed Decreased D 2 V/dt 2 At the Onsementioning
confidence: 99%
“…The SPON receives excitatory input from the contralateral ventral cochlear nucleus, mainly from octopus and multipolar cells (Warr 1966; Friauf and Ostwald 1988; Saldaña et al 1994; Schofield 1995). The timing of this input makes it a candidate mechanism for driving the onset response components in on-offset SPON units (Felix et al 2013). We found that on-offset units most often produce inhibited responses to the forward masking paradigm, whereas facilitated responses predominate in offset units.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to an excitatory input that originates mainly from the posteroventral cochlear nucleus (Felix et al 2013), the SPON receives strong, tonic glycinergic inhibitory input from the MNTB (Kulesza et al 2003; Kadner et al 2006; Kulesza et al 2007) and GABAergic inhibitory input from the tectal longitudinal column (TLC) (Viñuela et al 2011). The SPON provides a major source of GABAergic inhibition to neurons in the inferior colliculus (Kelly et al 1998; Kulesza and Berrebi 2000).…”
Section: Introductionmentioning
confidence: 99%